2016
DOI: 10.1038/ncomms10946
|View full text |Cite
|
Sign up to set email alerts
|

Spatial control of chemical processes on nanostructures through nano-localized water heating

Abstract: Optimal performance of nanophotonic devices, including sensors and solar cells, requires maximizing the interaction between light and matter. This efficiency is optimized when active moieties are localized in areas where electromagnetic (EM) fields are confined. Confinement of matter in these ‘hotspots' has previously been accomplished through inefficient ‘top-down' methods. Here we report a rapid ‘bottom-up' approach to functionalize selective regions of plasmonic nanostructures that uses nano-localized heati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 40 publications
1
55
0
Order By: Relevance
“…This easy, fast and cheap strategy could serve as a selective and large-scale method of positioning molecules/nanomaterials in a variety of plasmonic nanoantenna reactive spots or hot spots. Photo-polymerization49, three-photon absorption of disulphuric species50 or local solvent heating strategy51, among others, have been recently employed for high EM field hotspots modification. Here we have demonstrated that reactive spots can also be selectively accessed (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This easy, fast and cheap strategy could serve as a selective and large-scale method of positioning molecules/nanomaterials in a variety of plasmonic nanoantenna reactive spots or hot spots. Photo-polymerization49, three-photon absorption of disulphuric species50 or local solvent heating strategy51, among others, have been recently employed for high EM field hotspots modification. Here we have demonstrated that reactive spots can also be selectively accessed (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Second, plasmonic circular dichroism can be directly applied to study spin-dependent near-field effects. [3] Third, plasmonic circular dichroism can be transferred to other physical signals, such as asymmetric hot electron generation, [5,51] asymmetric heat generation, [79,91,97] and chiral optical forces. [98,99] Especially, the chiral photothermal effect enables the control of asymmetric thermal chemical processes.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…With their enhanced and compact super chiral fields generated by circularly polarized illumination, the MCMs enable the enantiodiscrimination of molecules with the higher sensitivity than the conventional techniques . The reliability and repeatability of this chiral sensing method have been confirmed by several publications . However, it is worth mentioning that the detection mechanism is still under debate since the intermediation of chiral electric and magnetic modes in a plasmonic nanostructure by biomolecules may also lead to the detection of chirality in molecules …”
mentioning
confidence: 99%